Brief Report: Pediatric Cancer Burden and Treatment Resources Within the Pediatric IeDEA Consortium. (1st September 2017) - Brown, Steven A.; Abbas, Salma; Davies, Mary-Ann; Bunupuradah, Torsak; Sohn, Annette H.; Technau, Karl-Günter; Renner, Lorna; Leroy, Valériane; Edmonds, Andrew; Yotebieng, Marcel; McGowan, Catherine C.; Duda, Stephany N.; et al.
Abstract : Introduction: The incidence and treatment of cancer in HIV-infected children from resource-limited settings has not been extensively studied. Objectives: Develop and implement a cross-sectional survey to evaluate pediatric cancer burden, diagnostic modalities in use, and treatment availability as perceived by HIV clinic staff at regional International Epidemiology Databases to Evaluate AIDS (IeDEA) sites. Methods: IeDEA regional investigators developed a cross-sectional clinical site survey which included questions on the numbers and types of pediatric cancers observed, modalities used to treat identified cancers, and treatment options available at individual sites in the Asia-Pacific, Latin America, Central Africa, East Africa, West Africa, and Southern Africa regions. Results: Kaposi sarcoma, non-Hodgkin lymphoma, and Burkitt lymphoma were reported by site personnel to be the most prevalent types of cancer in the pediatric HIV population. Survey results indicate that access to comprehensive cancer treatment modalities is very limited for children in these regions despite HIV care and treatment sites reporting that they diagnose pediatric cancers. Responses also showed that evaluating cancer in the pediatric HIV population is a challenge due to a lack of resources and varying treatment availability within regions. Conclusions: Further study is needed to increase our understanding of the changing epidemiology of cancer in HIV-infected pediatric populations. Increased financial and technical resources are critical to aid in the advancement of health services to support treatment of these children in resource-constrained settings.